2010
DOI: 10.3109/13685538.2010.518178
|View full text |Cite
|
Sign up to set email alerts
|

Androgen replacement therapy contributes to improving lower urinary tract symptoms in patients with hypogonadism and benign prostate hypertrophy: a randomised controlled study

Abstract: The status of human papillomavirus (HPV) infection in urothelial inverted papilloma was examined in the present study. Formalin-fixed and paraffin-embedded tissues from eight cases of inverted papilloma of the bladder were studied. The presence of HPV-DNA was examined by modified GP5/6+PCR using archival tissue sections by microdissection. HPV genotype was determined with a Hybri-Max HPV genotyping kit. Immunohistochemical analysis for p16-INK4a, mcm7, HPV-E4, and L1, and in situ hybridization (ISH) for the HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(78 citation statements)
references
References 50 publications
(30 reference statements)
6
67
1
2
Order By: Relevance
“…In contrast, some uncontrolled studies have reported a gradual improvement in the International Prostate Symptom Score (IPSS) following long-term testosterone therapy in men with hypogonadism and/or metabolic syndrome (MetS) (see review in Buvat et al (2010)). A small randomized controlled trial with testosterone enanthate in 23 men with BPH tends to support these findings, with a significant decrease in the IPSS score, maximum flow rate, and voided volume in the testosterone group but not in the 23 untreated controls (Shigehara et al 2011). However, in the present sample we did not find any difference in inflammation in BPH specimens from subjects treated or not with 5a-reductase inhibitors.…”
Section: Discussioncontrasting
confidence: 54%
“…In contrast, some uncontrolled studies have reported a gradual improvement in the International Prostate Symptom Score (IPSS) following long-term testosterone therapy in men with hypogonadism and/or metabolic syndrome (MetS) (see review in Buvat et al (2010)). A small randomized controlled trial with testosterone enanthate in 23 men with BPH tends to support these findings, with a significant decrease in the IPSS score, maximum flow rate, and voided volume in the testosterone group but not in the 23 untreated controls (Shigehara et al 2011). However, in the present sample we did not find any difference in inflammation in BPH specimens from subjects treated or not with 5a-reductase inhibitors.…”
Section: Discussioncontrasting
confidence: 54%
“…However, some prospective (Kristal et al 2008, Trifiro et al 2010 and cross-sectional studies (Schatzl et al 2000, Tan et al 2003, Roberts et al 2004, Miwa et al 2008, St Sauver et al 2011 have demonstrated an inverse association between serum testosterone and LUTS or BPH. Consistent with these observations, testosterone replacement therapy has been reported to relieve LUTS in hypogonadal men with both BPH (Holmäng et al 1993, Saad et al 2007, Kalinchenko et al 2008, Karazindiyanoglu & Ç ayan 2008, Amano et al 2010, Shigehara et al 2011 and MetS (Haider et al 2009).…”
Section: Introductionsupporting
confidence: 62%
“…Testosterone functions to keep males healthy and decreases gradually with age (7,8). Testosterone increases bone mineral density and muscle mass (9,10), improves mental function and cognitive impairment (11,12), decrease lower urinary tract symptoms and nocturia (13,14), and maintains cardiovascular health (15). On the other hand, androgen receptors in prostate cancer cells are important drivers of cancer progression and testosterone may be associated with carcinogenesis of prostate cancer and deteriorate benign prostate hyperplasia (16 -18).…”
Section: Discussionmentioning
confidence: 99%